Pengembangan Modul Ajar IPAS Berbasis PBL Materi Nilai Budaya Reog Ponorogo untuk Siswa Kelas IV - Sulistiana Dyah Kartika Putri; Surayanah Surayanah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
The need for teaching modules that are contextual and aligned with local culture serves as an important basis for developing Natural and Social Sciences (IPAS) learning in elementary schools, especially because the existing modules still tend to be general and insufficiently connected to students’ daily lives. This study aims to develop an IPAS teaching module based on Problem-Based Learning (PBL) on the cultural values of Reog Ponorogo to foster patriotism among Grade IV elementary school students. This study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 16 Grade IV students at SD Negeri 2 Bringin. The validity of the module was tested using the Gregory formula, practicality was analyzed based on the percentage of teacher responses, while effectiveness was tested through N-gain and a paired sample t-test based on pretest and posttest data. The results showed that the students’ average score increased from 26.44 in the pretest to 38 in the posttest. The effectiveness test results showed a significance value of 0.001, and the N-gain achievement was in the very high category. These findings indicate that the PBL-based IPAS teaching module on the cultural values of Reog Ponorogo was declared valid, practical, and effective in improving students’ understanding of local cultural values and is feasible for use in fostering patriotism among Grade IV elementary school students. This study provides a theoretical contribution to the development of literature on IPAS teaching modules that integrate PBL and local wisdom. Practically, this module can be used by teachers to create learning that is more contextual, meaningful, and closely connected to students’ lives, while also opening opportunities for the application of similar approaches in different subjects and levels of education.